Cleft Lip and Palate, the Initial Phase of Treatment Planning and Interdisciplinary Therapy for Patients in the Neonatal Age - J. Borský; M. Hubáček; J. Kozák; M. Kašparová; J. Fišer; T. Dostálová (Czech Dental Chamber, 2012)
Aim of Review: The purpose of this paper is to present a comprehensive overview of views on the treatment in patients with cleft lip and palate (CLP), primary lip repair, lip reconstruction in the neonatal period, including knowledge of fetal tissue healing. Background: Authors try to summarize the principles of stomato-orthodontic follow-up care. Orofacial clefts are the most common congenital developmental defects. Based on the statistical data, the mean incidence of all types of cleft defects in the orofacial area is 1.86 per 1000 live-born children Etiology is multifactorial. With respect to the range of the defect, the cooperation of a number of experts is required, and complicated and long-lasting therapies are necessary, especially for successful jaw growth. It is necessary to postpone a definitive solution to that time when the arches are in the growth phase. The multidisciplinary therapy involves the following disciplines: plastic surgery, orthodontics, speech pathology, psychology, otorhinolaryngology, genetics, pediatrics, and social work. Due to the extent of affliction, interdisciplinary co-operation is necessary and usually complicated and long-term therapy, which is needed especially for gradual growth of the jaw bones. Therefore, the final solution has to be postponed to a time when the arches are not in a growth period. The treatment should be initiated with a surgical lip correction (usually in the 3rd month of age of a child or fetal healing can be used) and later with a correction of the palate (between the 1st - 4th years of age). It should be followed by orthodontic therapy that optimally achieves correction (e.g. in an isolated palate cleft) but a final prosthetic solution is needed more often (especially in complex clefts). A favorable shape and size of the dental arches without anomalies is an important factor for the prosthetic phase. A cleft defect often means that some teeth are missing (lateral incisors, more often premolars) and there may be other orthodontic anomalies which include either crossed occlusion, inverse occlusion in the frontal part or various anomalies of a tooth position (inclination, rotation, etc.). Early prosthetic therapy (usually around 18 years of age) including implant insertion finalized treatment.